Peran Pendidikan Keluarga dalam Membina Perkembangan Sosial Emosional Anak Usia Dini di TK Al-Azhar Pagendingan - Fadilatul Karimah; Lailatul Firdausi (ISEDU : Islamic Education Journal, 2025)
Social-emotional development in early childhood is a foundational domain that shapes a child’s ability to regulate emotions, cooperate, and adapt to social rules. Within the framework of Islamic education, the family is regarded as the first school (madrasah al-ūlā) responsible for nurturing the child’s innate disposition (fitrah) through exemplary conduct (uswah hasanah), affectionate communication, and the habituation of noble character (akhlāq). This study aims to describe the role of family education in fostering the social-emotional development of Group A children at TK Al-Azhar Pagendingan. Employing a qualitative descriptive case-study design, data were collected through participant observation, in-depth interviews with parents, class teachers, and the principal, and documentation, then analyzed using the interactive model of Miles, Huberman, and Saldaña and validated through source and technique triangulation. The findings indicate that warm and consistent parenting, open family communication, parental modeling grounded in Islamic values, and sustained home–school collaboration are associated with children who express emotions constructively, cooperate with peers, and follow classroom routines with self-awareness. The study concludes that family education functions as the primary tarbiyah environment whose synergy with the school optimizes the social-emotional growth of young children.